2016
DOI: 10.1016/j.enbuild.2016.05.045
|View full text |Cite
|
Sign up to set email alerts
|

A virtual thermostat for local temperature control

Abstract: This thesis presents design and operation of a newly developed virtual thermostat to control any desired local temperature in an HVAC controlled space. Conventional HVAC thermostats use a single point temperature sensor at one fixed location in a controlled space to control the temperature of the whole space. The single point temperature sensor does not represent the entire controlled domain. In addition, in most applications only a small zone in the controlled space needs to be controlled (for example where t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
9
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(9 citation statements)
references
References 52 publications
(50 reference statements)
0
9
0
Order By: Relevance
“…An identification method based on ANN model was proposed to study multi-zone buildings while taking into account thermal interactions effects between neighboring zones (Huang et al 2015). An average temperature around an occupant, numerically obtained by CFD method, was feedback to a local ON/OFF controller to decrease energy consumption (Alhashme and Ashgriz 2016). Zhang et al (2018aZhang et al ( , 2019 proposed a dynamic temperature control based on multi-node model for both stratum ventilation and displacement ventilation.…”
Section: Introductionmentioning
confidence: 99%
“…An identification method based on ANN model was proposed to study multi-zone buildings while taking into account thermal interactions effects between neighboring zones (Huang et al 2015). An average temperature around an occupant, numerically obtained by CFD method, was feedback to a local ON/OFF controller to decrease energy consumption (Alhashme and Ashgriz 2016). Zhang et al (2018aZhang et al ( , 2019 proposed a dynamic temperature control based on multi-node model for both stratum ventilation and displacement ventilation.…”
Section: Introductionmentioning
confidence: 99%
“…5 It is not uncommon for heating and cooling flows, in the case of air conditioning systems, to be capable of rates of temperature change 5 to 10 times higher than surroundings heat loss/gains. 6,7 Even with a steady heat demand this creates a dynamic thermal environment where thermal energy is added to a space through the hydronic system until the flow is stopped when the room reaches its setpoint temperature (e.g. through a wall thermostat or thermostatic radiator valve, TRV).…”
Section: Introductionmentioning
confidence: 99%
“…The importance of what may appear only small changes to such cycling behaviour can have a significant influence on energy consumption (circa 15%). 7 In real-world scenarios where external temperatures, solar irradiance, meteorological conditions and occupant behaviours are fundamentally unsteady, the dynamic behaviour of the heating system is further exacerbated.…”
Section: Introductionmentioning
confidence: 99%
“…Madsen et al [14] observed a reduced fluctuation of the indoor temperature and a more constant temperature distribution across the room when the thermostat was placed in the centre of the room, compared to when it was placed on the wall. Alhasme and Ashgriz [15] simulated various temperature distributions within a room by using computational fluid dynamics (CFD) and reported that controlling the HVAC system based on the local temperature close to an occupant resulted in a 22% energy saving compared with a thermostat controlled from a single temperature sensor mounted on the wall. Huang et al [16] developed a CFD-aided method to generate a real-time temperature distribution of a room and optimize the location of wireless temperature sensors.…”
Section: Introductionmentioning
confidence: 99%